The effect of palliative care education by peers on pain management in cancer patients - Mojalli, Mohammad (2020)
The number of cancer patients is on the rise. Palliative care has an important role in improving the quality of life of these patients. Regarding the role of peers, this study aimed to evaluate the effect of peer care education by peers on pain management in cancer patients. In this clinical trial, 64 patients with cancer were selected as available, divided into control and intervention groups. The control group received usual educations and the intervention group received education package with pain management content by interested, educated and qualified peers in terms of education. The research instrument was pain management questionnaires that were filled before and 3 and 6 weeks after the intervention. Data were analyzed by SPSS software at the significant level of 0.05. The findings showed that the two groups were not significantly different in terms of age, sex, type of cancer, type of treatment, family history, occupation and education and were homogenous. The findings showed that pain management (from 11.78 to 22.59) was significantly different in the intervention group before and three and six weeks after the intervention (P <0.001). The effect of intervention of palliative care education by peers has increased the level of pain management among cancer patients. The findings of this study showed that palliative care education by peers affects the level of pain management in cancer patients. Getting help from interested and educated peers in pain management education for cancer patients is recommended.